DZIAŁALNOŚĆ USTAWODAWCZA KSIĘCIA MAZOWIECKIEGO JANUSZA I STARSZEGO 1381-1429 - Herod, Patrycja (Saeculum Christianum. Pismo Historyczne, 2017)
The article presents the legislative activity of Janusz I of Warsaw who from 1381 was an independent ruler of the Eastern Mazovia. It also offers an analysis of 15 legal instruments including 14 statutes and one landed privilege, which is the oldest known act of this type from the region of Mazovia delivered 21st June 1414 in Nowe Miasto for both the Czersk and Warsaw nobility. The article further deals with the division of specific regulations into criminal and private law, which includes marriage and family law, the law of succession, property law, obligations, the right of peasants to leave a village belonging to a feudal master as well as court proceedings. The article finishes with the presentation of the research results.